Legal Mechanisms for Carbon Trading in Indonesia: Accountability or Greenwashing? - Handipan H. Ali; Asrul Aswar (Universitas Negeri Gorontalo, 2026)
Indonesia has rapidly developed a legal framework for carbon trading, including Presidential Regulation No. 98 of 2021, its successor No. 110 of 2025, and the launch of the Indonesia Carbon Exchange. However, serious concerns persist regarding whether this framework ensures genuine environmental accountability or merely facilitates corporate greenwashing. This article employs a doctrinal legal research methodology, supplemented by comparative analysis with the California Cap and Trade program and case studies of Indonesian offset projects. The analysis reveals two fundamental weaknesses. First, accountability mechanisms, including monitoring, reporting, and verification, lack independence. Reversal liability rules for forest based credits are absent, and no dedicated dispute resolution body exists. Second, the framework contains no mitigation hierarchy, no anti greenwashing provisions, and no mandatory disclosure of credit types or retirement dates. These structural flaws enable companies to claim carbon neutrality without meaningful internal decarbonisation. The article concludes that Indonesia's carbon trading mechanism currently prioritises market formation over environmental integrity. Urgent reforms are recommended, including an independent verification body, a binding mitigation hierarchy, and explicit anti greenwashing rules. Without such reforms, carbon trading risks becoming a tool for reputational laundering rather than genuine climate action.